Book Review: Gift & Giver: The Holy Spirit for Today - John Paul Lathrop (Sekolah Tinggi Theologia Jaffray, 2017)
Dr. Craig Keener has established himself as a highly respected New Testament scholar. Over the years he has written a number of very significant commentaries including works on the gospels of Matthew and John, and the book of Acts. His highly acclaimed IVP Bible Background Commentary: New Testament is one of his best known works. In addition, he has produced books devoted to specific biblical topics such as miracles, women in marriage and ministry, and divorce and remarriage. He is not one to shy away from controversial subjects. In this present volume Keener writes about the Holy Spirit including the sometimes controversial charismatic aspects of His ministry. Gift & Giver was first published in theUnited States in 2001. More recently it has been translated into Indonesian and published inIndonesia.